Неравенства типа Джексона при приближении периодических функций полиномами Фейера, Рогозинского и Коровкина - Божуха, Л.Н. (Український математичний журнал, 2000)
Розглядаються нерівності типу Джексона при наближенні періодичних функцій у просторі L2 лінійними середніми їх рядів Фур'є. При розв'язуванні задачі як мажоранта квадрата відхилення вибирається інтеграл від квадрата модуля неперервності. Виявлено, що для поліномів Фейєра і Рогозинського константа така ж, як і у випадку найкращого наближення, а для поліномів Коровкіна більша. We consider inequalities of the Jackson type in the case of approximation of periodic functions by linear means of their Fourier series in the space L 2. In solving this problem, we choose the integral of the square of the modulus of continuity as a majorant of the square of the deviation. We establish that the constants for the Fejér and Rogosinski polynomials coincide with the constant of the best approximation, whereas the constant for the Korovkin polynomials is greater than the constant of the best approximation.